Enhanced methane separation composite membrane and preparation method thereof

By using the composite structure of the carrier layer, intermediate layer and surface cortex in the methane separation membrane, the problem of lack of selectivity and mechanical properties on the molecular scale of traditional membrane separation methods is solved, and efficient separation of methane and nitrogen and mechanical are achieved. The combination of strength is suitable for low concentration methane separation applications and simplifies the preparation process.

CN119139934APending Publication Date: 2024-12-17LIAONING UNIVERSITY OF PETROLEUM AND CHEMICAL TECHNOLOGY +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411365562.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

It is difficult to effectively separate methane and nitrogen in low-concentration coalbed methane. Traditional membrane separation methods lack selectivity on the molecular scale, and it is difficult to take into account the mechanical properties of membrane materials and the gas permeability of gases.

Method used

A composite membrane structure consisting of a carrier layer, an intermediate layer and a surface cortex is adopted, where the carrier layer is a polytetrafluoroethylene porous membrane, the intermediate layer is composed of nano-scale inorganic particles, and the surface cortex is a block polymer resin layer, which is synthesized by hydrothermal heat. Prepare with ultrasonic cleaning and other steps to form a methane separation composite film with uniform surface, uniform thickness and high mechanical strength.

Benefits of technology

It significantly improves the separation selectivity between methane and nitrogen, maintains a high gas permeability flux and mechanical strength, is suitable for low-concentration methane separation applications, and simplifies the preparation process, reduces costs, and promotes industrial application.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the field of release membranes and preparation thereof, and particularly relates to an enhanced methane separation composite membrane and a preparation method thereof. The composite membrane sequentially comprises a carrier layer, a middle layer and a surface skin layer which are organically combined to form a whole, the carrier layer is a polytetrafluoroethylene porous membrane, the middle layer is composed of nanoscale inorganic particles, and the surface skin layer is a block polymer resin layer. The preparation method comprises the following steps: carrying out ultrasonic-assisted cleaning on a polytetrafluoroethylene porous membrane in a mixed solution of ethanol and water in sequence, and then treating with a sodium naphthalene solution; dipping the obtained carrier layer in a precursor-containing solution, and carrying out hydrothermal reaction to realize in-situ generation of a middle layer in the carrier; and placing the obtained product in a resin solution, keeping for a certain time under a certain vacuum degree, and then drying to obtain the target product enhanced methane separation composite membrane. The composite membrane is uniform in surface, uniform in thickness, good in mechanical strength and high in stability, the gas permeation flux of the composite membrane is equivalent to that of a methane separation membrane prepared by a traditional method, but the gas separation selectivity of the composite membrane is ideal.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of separation membranes and preparation thereof, and particularly relates to an enhanced methane separation composite membrane and a preparation method thereof. Background Art

[0002] According to the provisions of my country's "Coal Mine Safety Regulations", when utilizing coalbed methane, the CH4 concentration must be greater than 30% to be economical. Therefore, the enrichment of methane resources in low-concentration coalbed methane has become an important issue facing the world. CH4 and N2 are the main components of low-concentration coalbed methane. At room temperature and pressure, their properties are similar and difficult to separate. Compared with traditional methods, gas membrane separation technology is simple, easy to operate, low cost, and has no secondary pollution. Its effect is highly dependent on membrane technology. The transfer mechanism of gas molecules in the membrane includes dissolution-diffusion, viscous flow, Knudsen diffusion, surface diffusion, capillary condensation, and molecular sieving. The dissolution-diffusion mechanism assumes that the gas permeation process is achieved through three steps: (1) gas adsorption and dissolution on the membrane surface; (2) gas dissolved on the membrane surface diffuses to the permeation side driven by the concentration gradient; (3) gas desorbs on the other side of the membrane. When the membrane pore diameter is much larger than the mean free path of gas molecules, the gas transfer mechanism through the membrane pore is viscous flow, and the membrane has no selectivity for gas.

[0003] With the successful application of membrane nitrogen enrichment and oxygen enrichment technologies in the industrial field in recent years, it has become possible to develop a membrane separation process for CH4-N2. At present, there are many literature reports on the research of separation membrane materials for CH4 gas enrichment and purification, but large-scale membrane separation is still in the development stage, especially for the CH4-N2 system, there are still a lot of basic problems to be solved in membrane separation. When the membrane pore diameter is smaller than the mean free path of gas molecules, the frequency of collision between molecules and pore walls is greater than the frequency of collision between molecules, and the gas transmission mechanism through the membrane pores is Knudsen diffusion. At this time, the ideal separation factor of CH4 / N2 is only 1.32, and effective separation cannot be achieved. Therefore, the separation membrane used for the CH4-N2 system should be designed as a non-porous or extremely small pore structure, and for coalbed methane with low methane concentration, the membrane material should be a membrane that preferentially permeates CH4 molecules. On the other hand, there is a certain contradiction between the thickness of the membrane material and the gas permeability and mechanical properties, which needs to be systematically solved by designing a new membrane structure and selecting a suitable membrane-forming material. Summary of the invention

[0004] The present invention aims to overcome the shortcomings of the prior art and provide a composite membrane with uniform surface, uniform thickness, good mechanical strength and strong stability. Its gas permeation flux is equivalent to that of methane separation membranes prepared by traditional methods, but its gas separation selectivity is ideal, and its preparation method is an enhanced methane separation composite membrane.

[0005] To solve the above technical problems, the present invention is achieved as follows: An enhanced methane separation composite membrane comprises a carrier layer, an intermediate layer and a surface layer in sequence, and the three membrane layers are organically combined to form a whole; the carrier layer is a polytetrafluoroethylene porous membrane, the intermediate layer is composed of nanometer-level inorganic particles, and the surface layer is a block polymer resin layer.

[0006] The method for preparing the enhanced methane separation composite membrane comprises the following steps: (1) Preparation of the carrier layer: the polytetrafluoroethylene porous membrane is ultrasonically cleaned in a mixed solution of ethanol and water, then treated with a sodium naphthalene solution, and finally rinsed with deionized water and dried for use; (2) hydrothermal synthesis of the intermediate layer, immersing the carrier layer obtained in step (1) in a precursor solution, achieving in-situ generation of the intermediate layer inside the carrier through a hydrothermal reaction, and finally rinsing and drying for use; (3) Preparation of the surface skin layer: placing the product obtained in step (2) in a resin solution, maintaining it under a certain vacuum for a certain period of time, and then drying it to obtain the target product, an enhanced methane separation composite membrane.

[0007] Furthermore, the carrier layer has an average pore size of 0.5 to 1.0 μm and a thickness of 5 to 20 μm.

[0008] Furthermore, the intermediate layer is composed of a granular metal organic framework material, which is attached to the inside of the carrier layer and has a particle size of 0.1 to 2 μm.

[0009] Furthermore, the surface skin layer is composed of a triblock polymer.

[0010] Furthermore, the surface skin layer is composed of styrene-butadiene-styrene triblock polymer.

[0011] Furthermore, in step (2), the precursor solution contains metal ions and organic ligands.

[0012] Furthermore, in step (2), the precursor solution is prepared by adding nickel nitrate hexahydrate to a mixed solution of deionized water and tetrahydrofuran. Furthermore, when the thickness of the methane separation composite membrane is 15 to 30 μm, the tensile strength of the membrane is 23 to 35 MPa, and the methane permeation flux of the membrane for separating equal volumes of methane and nitrogen mixed gas is 122 to 164 Barrer, and the separation selectivity of methane and nitrogen is 3 to 4.

[0013] The composite membrane prepared by the present invention has a uniform surface and thickness, and its gas permeation flux is comparable to that of the methane separation membrane prepared by the traditional method, but its gas separation selectivity is significantly improved, and it has great application potential in the field of mixed gas separation. At the same time, the preparation technology of the present invention is simple and easy to implement, low in cost, environmentally friendly, and easy to achieve large-scale production. An enhanced methane separation composite membrane obtained according to the above method has a thinner thickness, higher mechanical strength, and no surface defects. It shows a higher gas permeation flux and separation factor, and has a lower material cost, which has a significant promoting effect on promoting the industrial application of methane gas separation composite membranes. The preparation method of the enhanced methane separation composite membrane of the present invention is simple in process, does not require special equipment, and can also be extended to the preparation of other types of gas separation membranes. DETAILED DESCRIPTION

[0014] The present invention will be described in detail below through specific examples. These examples are provided in order to enable a more thorough understanding of the present invention and to fully convey the scope of the present invention to those skilled in the art. As mentioned throughout the specification and claims, "including" or "comprising" is an open term, interpreted as "including but not limited to". The subsequent description of the specification is a preferred embodiment of the present invention, but the description is based on the general principles of the specification and is not intended to limit the scope of the present invention. The scope of protection of the present invention shall be subject to the definition of the attached claims. Unless otherwise specified, the various reagents and materials used in the present invention can be purchased from the market. In the present invention, unless otherwise specified, the percentages involved are all mass percentages.

[0015] Example 1 Pretreatment of the carrier: a polytetrafluoroethylene porous membrane with an average pore size of 0.5 μm, a thickness of 15 μm, and a porosity of 90%. It was immersed in an excess of ethanol and water mixed solution (volume ratio 1:1), treated in an ultrasonic cleaner with a power of 350 W for 30 min, and then dried at 100 °C. The carrier was immersed in a commercially available sodium naphthalene solution again, kept at room temperature for 30 s, taken out and rinsed in excess deionized water for 20 min, and then dried at 60 °C for use.

[0016] Hydrothermal synthesis of functional layer: 350 mL of deionized water and tetrahydrofuran were measured and mixed. Nickel nitrate hexahydrate (13.06 g) and 2,5-dihydroxyterephthalic acid (5.22 g) were added and stirred for 2 h to obtain a precursor solution. 60 mL of the precursor solution and a polytetrafluoroethylene membrane of a certain size were placed in a polytetrafluoroethylene hydrothermal autoclave, sealed and reacted at 140 °C in a microwave for 2.0 h, rinsed with deionized water, and dried for use.

[0017] Composite resin cortex: A 15% SBS resin solution was prepared, and the polytetrafluoroethylene carrier with a functional layer was immersed in the resin solution. The solution was kept at a vacuum degree of 0.8 MPa for 3 min, and then dried at 80 °C for 6 h to complete the preparation of the composite membrane.

[0018] Comparative Example 1 A pure resin film with a thickness of about 30 μm was prepared by a casting method using a SBS resin solution with a concentration of 15%. The drying temperature and time were the same as those in Example 1.

[0019] Comparison of properties between the inventive film of Example 1 and the comparative film of Comparative Example 1: The thickness of the invention membrane and the comparative membrane is similar, about 30μm, the tensile strength of the invention membrane is 35 MPa, and the strength of the comparative membrane is 12 MPa. Gas separation performance: for separation of a 1:1 mixed gas of methane and nitrogen, the methane permeation flux of the invention membrane reaches 122 Barrer, and the methane / nitrogen separation selectivity is 3.7, while the methane permeation flux of the comparative membrane is 173 Barrer, and the methane / nitrogen separation selectivity is 1.3.

[0020] Example 2 Pretreatment of the carrier: a polytetrafluoroethylene porous membrane with an average pore size of 1.5 μm, a thickness of 25 μm, and a porosity of 80%. It was immersed in an excess of ethanol and water mixed solution (volume ratio 1:1), treated in an ultrasonic cleaner with a power of 350 W for 10 min, and then dried at 100 °C. The carrier was immersed in a commercially available sodium naphthalene solution again, kept at room temperature for 120 s, taken out and rinsed in excess deionized water for 20 min, and then dried at 80 °C for use.

[0021] Hydrothermal synthesis of functional layer: 350 mL of deionized water and tetrahydrofuran were measured and mixed. Nickel nitrate hexahydrate (26.12 g) and 2, 5-dihydroxyterephthalic acid (10.44 g) were added and stirred for 2 h to obtain a precursor solution. 60 mL of the precursor solution and a polytetrafluoroethylene membrane of a certain size were placed in a polytetrafluoroethylene hydrothermal autoclave, sealed and reacted at 100 ° C in a microwave for 6.0 h, rinsed with deionized water, and dried for use.

[0022] Composite resin to form skin layer: Prepare SBS resin solution with a concentration of 5%, immerse the polytetrafluoroethylene carrier with functional layer into the resin solution, keep it under vacuum degree of 0.2MPa for 10 min, and then 100 o C for 6 h to complete the preparation of the composite membrane.

[0023] Comparative Example 2 A pure resin film with a thickness of about 20 μm was prepared by a casting method using a 5% SBS resin solution. The drying temperature and time were the same as those in Example 1.

[0024] Comparison of properties between the inventive film of Example 1 and the comparative film of Comparative Example 1: The thickness of the invention membrane and the comparative membrane is similar, about 20 μm, the tensile strength of the invention membrane is 26 MPa, and the strength of the comparative membrane is 7 MPa. Gas separation performance: for separation of a 1:1 mixed gas of methane and nitrogen, the methane permeation flux of the invention membrane reaches 164 Barrer, and the methane / nitrogen separation selectivity is 3.2, while the methane permeation flux of the comparative membrane is 257 Barrer, and the methane / nitrogen separation selectivity is 1.0.

[0025] Example 3 Pretreatment of the carrier: a polytetrafluoroethylene porous membrane with an average pore size of 1.0 μm, a thickness of 5 μm, and a porosity of 95%. It was immersed in an excess of ethanol and water mixed solution (volume ratio 1:1), treated in an ultrasonic cleaner with a power of 350 W for 15 min, and then dried at 100 °C. The carrier was immersed in a commercially available sodium naphthalene solution again, kept at room temperature for 50 s, taken out and rinsed in excess deionized water for 20 min, and then dried at 60 °C for use.

[0026] Hydrothermal synthesis of functional layer: 350 mL of deionized water and tetrahydrofuran were measured and mixed. Nickel nitrate hexahydrate (20.12 g) and 2, 5-dihydroxyterephthalic acid (12.44 g) were added and stirred for 2 h to obtain a precursor solution. 60 mL of the precursor solution and a polytetrafluoroethylene membrane of a certain size were placed in a polytetrafluoroethylene hydrothermal reactor, sealed and reacted at 160 ° C in a microwave for 1.5 h, rinsed with deionized water, and dried for use.

[0027] Composite resin to form skin layer: Prepare SBS resin solution with a concentration of 35%, immerse the polytetrafluoroethylene carrier with functional layer into the resin solution, keep it under vacuum degree of 1.0 MPa for 5 min, and then 100 o C for 12 h to complete the preparation of the composite membrane.

[0028] Comparative Example 3 A pure resin film with a thickness of about 15 μm was prepared by a casting method using a 35% SBS resin solution. The drying temperature and time were the same as those in Example 1.

[0029] Comparison of properties between the inventive film of Example 1 and the comparative film of Comparative Example 1: The thickness of the invention membrane and the comparative membrane is similar, about 15μm, the tensile strength of the invention membrane is 30 MPa, and the strength of the comparative membrane is 16MPa. Gas separation performance: separation of methane: nitrogen = 1:1 mixed gas, the methane permeation flux of the invention membrane reaches 158 Barrer, the methane / nitrogen separation selectivity is 3.54, the methane permeation flux of the comparative membrane is 209 Barrer, and the methane / nitrogen separation selectivity is 1.1.

[0030] Example 4 Pretreatment of the carrier: a polytetrafluoroethylene porous membrane with an average pore size of 0.7 μm, a thickness of 18 μm, and a porosity of 85%. It was immersed in an excess of ethanol and water mixed solution (volume ratio 1:1), treated in an ultrasonic cleaner with a power of 350 W for 15 min, and then dried at 100 °C. The carrier was immersed in a commercially available sodium naphthalene solution again, kept at room temperature for 20 s, taken out and rinsed in excess deionized water for 20 min, and then dried at 80 °C for use.

[0031] Hydrothermal synthesis of functional layer: 350 mL of deionized water and tetrahydrofuran were measured and mixed. Nickel nitrate hexahydrate (15.64 g) and 2, 5-dihydroxyterephthalic acid (7.38 g) were added and stirred for 2 h to obtain a precursor solution. 60 mL of the precursor solution and a polytetrafluoroethylene membrane of a certain size were placed in a polytetrafluoroethylene hydrothermal autoclave, sealed and reacted at 130 ° C in a microwave for 13.5 h, rinsed with deionized water, and dried for use.

[0032] Composite resin to form skin layer: Prepare SBS resin solution with a concentration of 12%, immerse the polytetrafluoroethylene carrier with functional layer into the resin solution, keep it under vacuum degree of 0.6MPa for 20 min, and then 80 o C for 12 h to complete the preparation of the composite membrane.

[0033] Comparative Example 4 A pure resin film with a thickness of about 26 μm was prepared by a casting method using a SBS resin solution with a concentration of 12%. The drying temperature and time were the same as those in Example 1.

[0034] Comparison of properties between the inventive film of Example 1 and the comparative film of Comparative Example 1: The thickness of the invention membrane and the comparative membrane is similar, about 26μm, the tensile strength of the invention membrane is 23MPa, and the strength of the comparative membrane is 11MPa. Gas separation performance: separation of methane: nitrogen = 1:1 mixed gas, the methane permeation flux of the invention membrane reaches 125Barrer, the methane / nitrogen separation selectivity is 3.65, the methane permeation flux of the comparative membrane is 172Barrer, and the methane / nitrogen separation selectivity is 1.3.

[0035] The results of the examples show that the enhanced methane separation composite membrane and its preparation method provided by the present invention overcome the temperature that is difficult to balance between the structure and gas permeability of the composite membrane material for traditional methane separation. By introducing a porous reinforced skeleton material, the mechanical strength of the composite membrane can be ensured to be sufficiently high while maintaining the thickness of the thin film layer, and the defects caused by the deformation of the membrane layer due to factors such as pressure during the use of the membrane material can be met. At the same time, the membrane preparation method of the present invention is relatively simple, which is conducive to further mass production and provides a certain guarantee for the development of low-concentration methane separation and enrichment technology.

[0036] It is understandable that, for ordinary technicians in this field, various other corresponding changes and extensions can be made based on the technical methods of the present invention, and all these changes and extensions should fall within the protection scope of the claims of the present invention.

Claims

1. An enhanced methane separation composite membrane, It is characterized in that The composite membrane comprises a carrier layer, an intermediate layer and a surface layer in sequence, and the three membrane layers are organically combined to form a whole; the carrier layer is a polytetrafluoroethylene porous membrane, the intermediate layer is composed of nanometer-level inorganic particles, and the surface layer is a block polymer resin layer.

2. The method for preparing the enhanced methane separation composite membrane according to claim 1, It is characterized in that The steps include: (1) Preparation of the carrier layer: the polytetrafluoroethylene porous membrane is ultrasonically cleaned in a mixed solution of ethanol and water, then treated with a sodium naphthalene solution, and finally rinsed with deionized water and dried for use; (2) hydrothermal synthesis of the intermediate layer, immersing the carrier layer obtained in step (1) in a precursor solution, achieving in-situ generation of the intermediate layer inside the carrier through a hydrothermal reaction, and finally rinsing and drying for use; (3) Preparation of the surface skin layer: placing the product obtained in step (2) in a resin solution, maintaining it under a certain vacuum for a certain period of time, and then drying it to obtain the target product, an enhanced methane separation composite membrane.

3. The method for preparing the enhanced methane separation composite membrane according to claim 2, Features: The carrier layer has an average pore size of 0.5 to 1.0 μm and a thickness of 5 to 20 μm.

4. The method for preparing the enhanced methane separation composite membrane according to claim 3, Features: The intermediate layer is composed of granular metal organic framework material, attached to the inside of the carrier layer, and has a particle size of 0.1 to 2 μm.

5. The method for preparing the enhanced methane separation composite membrane according to claim 4, Features: The surface skin layer is composed of a triblock polymer.

6. The method for preparing the enhanced methane separation composite membrane according to claim 5, Features: The surface skin layer is composed of styrene-butadiene-styrene triblock polymer.

7. The method for preparing the enhanced methane separation composite membrane according to claim 6, Features: In step (2), the precursor solution contains metal ions and organic ligands.

8. The method for preparing the enhanced methane separation composite membrane according to claim 6, Features: In step (2), the precursor solution is prepared by adding nickel nitrate hexahydrate to a mixed solution of deionized water and tetrahydrofuran.

9. The method for preparing the enhanced methane separation composite membrane according to any one of claims 1 to 9, Features: When the thickness of the methane separation composite membrane is 15 to 30 μm, the tensile strength of the membrane is 23 to 35 MPa, and the methane permeation flux of the membrane for separating equal volumes of methane and nitrogen mixed gas is 122 to 164 Barrer, and the separation selectivity of methane and nitrogen is 3 to 4.

Citation Information

Cited By

  • MOF mixed matrix membrane for methane purification and preparation method thereof

    CN122209244A